Social Media for Consumers and Value Creation Companies - Bayezid Muraz (Global Writing Academica Researching and Publishing, 2022)
In the mid-2000s, a digital marketing strategy gave numerous companies online prominence. Amazon posts unfavorable customer reviews on evaluation sites, while many corporations use email. Few people paid attention to digitalization's marketing advancements. Since 2006, when Facebook opened to the public, social media has influenced consumers and businesses. This trend is accelerating. Facebook, Google, and YouTube - live social networking sites or platforms with strong social networking aspects - had the most traffic in the summer of 2013. One in seven people in the globe are active Facebook members, despite being restricted to those over 13 and banned in China. Marketing managers and experts are just beginning to appreciate social media's explosive growth. It affected their beginning. The pinball analogy argues that social media marketing is chaotic and dynamic, replacing the bowling technique, which is linear and one-way. The pin-table example explains how value creation processes and structures might adapt to new marketing environments if organizations are to be regarded as profitable by active, highly connected consumers via networks. This study presents a fresh environment overview and important thoughts on marketing managers and enterprises.